2011
DOI: 10.1007/s00216-011-5504-3
|View full text |Cite
|
Sign up to set email alerts
|

On the stability of the bioactive flavonoids quercetin and luteolin under oxygen-free conditions

Abstract: The natural flavonoid compounds quercetin (3,3',4',5,7-pentahydroxyflavone) and luteolin (3',4',5,7-tetrahydroxyflavone) are important bioactive compounds with antioxidative, anti-allergic, and anti-inflammatory properties. However, both are unstable when exposed to atmospheric oxygen, which causes degradation and complicates their analytical determinations. The oxidative change of these flavonoids was observed and followed by UV-visible spectrophotometry, both in aqueous and ethanolic solutions. The distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
53
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 95 publications
(60 citation statements)
references
References 37 publications
5
53
0
2
Order By: Relevance
“…Quercetin has two different pharmacophores: the catechol group in ring B and the three hydroxyl groups in rings A and C, of which the catechol moiety is the most reactive one where deprotonation occurs easily [51,52]. The pK a values of quercetin are 5.87 and 8.48 [16,53]. The pK a values for the phenolic-OH group in phenol, p-coumaric acid, ferulic acid and thymol are 10, 9.5, 9.4, and 10.6, respectively [51,53,54].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Quercetin has two different pharmacophores: the catechol group in ring B and the three hydroxyl groups in rings A and C, of which the catechol moiety is the most reactive one where deprotonation occurs easily [51,52]. The pK a values of quercetin are 5.87 and 8.48 [16,53]. The pK a values for the phenolic-OH group in phenol, p-coumaric acid, ferulic acid and thymol are 10, 9.5, 9.4, and 10.6, respectively [51,53,54].…”
Section: Resultsmentioning
confidence: 99%
“…As far as phenols are concerned they are in the undissociated form at low pH, i.e., pH < pK a , but they are in the form of phenolate ions at high pH, i.e., pH > pK a . Further in more acidic condition, the reducing capacity of the phenols may be suppressed due to protonation, whereas in more basic condition, the reducing capacity of the phenols enhances due to the formation of phenolate ions [16,17]. When the phenols are in the undissociated form, the formation of phenoxyl radical involves the removal of hydrogen atom.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that the presence of atmospheric oxygen causes photodegradation in many flavonoids, decreasing their biological properties, including their luminescence/fluorescence [70][71][72]. In this regard, some authors have claimed that the dye performance can be affected when is attached to the surface of carriers, e.g., it causes spectral shifts of both absorption and emission, it affects photo stability, and it alters the fluorescence lifetime [73][74][75][76].…”
Section: Photoluminescence Of Epef Compounds and Nps-aptes-epefmentioning
confidence: 99%
“…There are many studies dealing with estimation of dissociation constant in the literature. The controversy reported on the acid-base properties of both flavonoids was explained by strong influence of the oxygen on the stability of their dissociation forms in our recent paper 7,8 . We reported values of dissociation constant pK 1 = 5.87 ± 0.14 and pK 2 = 8.48 ± 0.09 of quercetin and pK 1 = 5.99 ± 0.32 and pK 2 = 8.40 ± 0.42 of luteolin, which were found under strict anaerobic conditions.…”
mentioning
confidence: 92%